Gradientes da vulnerabilidade à contaminação aquífera do Parque Nacional/ Vila de Jericoacoara/CE - Braga, Macelma de Oliveira (2018)
This paper deals with the hydrogeological conditions and vulnerability of the jericoacoara national park (parna) / Vila de Jericoacoara, located in the municipality of Jijoca de Jericoacoara, on the Northwest coast of the State of Ceará. The PARNA of Jericoacoara was created in february 2002. The aquifers of the region are divided into sedimentary aquifers (dunes and barreiras system) and fissure aquifer. However, the supply of the village of Jericoacoara comes from the sedimentary aquifers. The use of these aquifer systems should be rationalized to avoid problems related to overexploitation and, or contamination, in this context the mapping of vulnerability is an important tool for the preservation of these resources. Aquifer vulnerability means its greater or lesser susceptibility to being affected by an imposed contaminant load. It is an intrinsic property of the aquifer. In this work the god Method of Foster and Hirata (2006) was adopted as methodological model. Where 55 wells were cataloged, 28 through the underground water information system - SIAGAS of the Mineral Resources Research Company - CPRM and 27 wells registered by Forte and Abreu, 2017 in the field. The indices found in the area vary from medium to high. According to the vulnerability gradients the area was classified into sectors, sector i - area consisting of porous sedimentary material and superficiality of the terrain - high vulnerability; sector II - medium to high vulnerability because they are constituted by porous and non-consolidated less superficial sediments. In the mapping of the uses in the PARNA, it was possible to define six (6) environmental units, being: fixed dunes, mobile dunes, receiving beaches, plain flúviomarinha, serrote and interdunar depression, existing a predominance of the dunes field. Among the main potentially impacting activities were identified: the great concentration of residential and tourist centers in the village, the presence of two cemeteries, catchments outside ABNT standards, wells functioning without proper granting, non-adherence of part of the population to the sewage treatment system, as well as, the inadequate position and currently the high demand of the sewage treatment plant. Because it is a conservation unit, these impacts become even more aggravating.